(untitled) (Gestão & Regionalidade, 2016)
The public policies have been studied from different theoretical and technical aspects, however, there is still a gap involvingseveral issues related to the intersectorality and integration of governmental actions. This article sought to identify wherethat disjoined character occurs, from the literature on intersectionality to explain, through documentary research, this dissociationbetween the official character of the coordinated action and practice of fragmented implementation. For that end,besides the the theoretical debate that incorporates different categories of political science, public administration, publicpolicies, geography and economics, the study was based on secondary sources, using databases of various governmentagencies to gather information. The purpose of the article is to contribute to the construction of a methodology that allowsto understand some of these intersectoral performance limits starting from dimensions little addressed in the studies.